Conceptions and practices of assessment in higher education: a study of Portuguese university teachers - Pereira, Diana Alexandra Ribeiro (2016)
This paper looks at how Portuguese university teachers look at assessment in Higher Education. It focuses on their conceptions and methods of assessment. Data were collected through face to face interviews and online open-ended questionnaires in five Portuguese Public Universities in different fields of knowledge. In total, 57 teachers participated in this study. Findings are presented according to the emerging categories arising from the data analysis: i) university teachers’ conceptions of assessment; ii) most used assessment methods; iii) role of assessment; iv) key moments in which assessment is put into practice. Implications of the findings are discussed.